Synthesis of nanocomposite CaxZny(OH)2(x + y) as thermochemical storage material. Issue 2 (26th November 2015) - Hu, Jun; Sun, Shiming; Yu, Lijun; Zheng, Maosheng
Abstract : Thermal energy storage has good application prospects. Thermochemical storage is one of the interesting methods for long-term storage as it can store energy at room temperature without any loss. This experiment investigates a method to synthesize expanded graphite-based Ca x Zn y (OH)2( x  +  y ) in ammonia (NH3 )/ammonium chloride (NH4 Cl) solution for solar energy storage. Scanning electron microscopy, thermal gravimetric analysis and X-ray diffraction are used to characterize the properties of the material. The results show that calcium hydroxide (Ca(OH)2 ) and zinc hydroxide (Zn(OH)2 ) in the expanded graphite composite are disposed at the nanolevel. Specifically, the crystal size of composite material ranges from 29·9 to 47·3 nm. The structure of the expanded graphite that adsorbed the nanocomposite material of Ca x Zn y (OH)2( x  +  y ) is porous. Furthermore, the decomposition temperature of expanded graphite-based Ca x Zn y (OH)2( x  +  y ) was nearly 171·6°C, which will significantly and effectively improve the reaction rate of thermal decomposition.